Desenvolvimento de uma framework de business performance management - Natálio, João Tiago Ribeiro Mendes (2011)
This document describes in detail all work performed on stage during nine months in the company GEDI (Gabinete de Estudos e Divulgação Informática, SA) by student João Tiago Ribeiro Mendes Natálio in the Computer Engineering Project at Faculdade de Ciências da Universidade de Lisboa. This work involves a software development project which will create a Business Intelligence Framework focused on the area of Business Performance Management and which will serve as an important tool for decision support to the organizations. The Business Performance Management Framework aims to help organizations in the efficient use of their financial resources, human capital, materials and other resources. We developed a flexible system capable of gathering information from several different data sources through the application of ETL (Extract, Transform and Load) techniques for the construction of several Data Warehouses, which works seamlessly with the Sistema Integrado de Apoio à Gestão para a Administração Pública developed by GEDI. The data analysis and exploration features of SIAG-AP were upgraded to support data exploration over data sources selected by the end users, features that rely on Mondrian, an OLAP (Online Analytical Processing) engine developed by Pentaho. The developed project provides various features of exploration and data analysis, as well as providing metrics and management indicators related to business processes.